Analisis Kepuasan Masyarakat Terhadap Pelayanan JNE - Ela Kurnia; Wisnu Sagantara; Syamsul Hidayat (Student Research Journal, 2024)
The aim of this research is to find out how the quality of goods delivery or courier services affects JNE customer satisfaction. The population of this research is consumers who use JNE delivery services. The technique used in collecting data is using Google Form. The first stage we carried out was distributing the questionnaire URL via Whatapps to people who use JNE courier services. The target we hoped for was 100 respondents, and we managed to get it in approximately 3 weeks. In this research, there are 10 indicator questions that respondents must fill in, with each choice having a different weight. The research results show that the service elements in the index are in the very satisfied service interval for each indicator, courier discipline, courier responsibility, courier service ability, courier politeness and friendliness, conformity of fees paid with predetermined prices and accuracy in implementing the service time schedule. The results of the research are in the form of information that can be used to further improve the quality of JNE services so that it can achieve JNE's goals and vision.